Suvarnabhumi : Study and interpret from scriptures - Nakkanrian, Manop; Kinasen, Winyou; Nakkanrian, Banchuen; Saramart , Chatsuphang (Journal of Contemporary Buddhist Society = JCBS, 2025)
Suvarnabhumi is a land of one of the civilizations of the Eastern world, similar to the ancient Chinese and ancient Indian civilizations. It is a trading center where Indian merchants traveled to trade. It is the land where Buddhism was first established outside of India, led by Phra Sonathera and Phra Uttarathera, which occurred after the 3rd Buddhist Council in the 3rd century, with Phra Mokkalliputtissa Thera as the president, under the patronage of King Ashoka the Great. It is considered the first of the 4 eras of Buddhism in Thailand, called the Theravada era of the Asoka period. Studying and interpreting the history of the spread of Buddhism to Suvarnabhumi using the Samantapasadika, Mahavamsa, and Dipavamsa scriptures has led to various issues, such as the sending of monks to proclaim Buddhism in various places, Phra Sonathera and Phra Uttarathera as Buddhist missionaries, Raksa woman - water giantess - demon, Phra Sonathera and Phra Uttarathera are just legends or real people in history and the development of the monarchy system according to Indian beliefs.